"\\displaystyle\n\n\\frac{\\mathrm{d}y}{\\mathrm{d}x} = -\\frac{x + 2y - 3}{2x + y - 3}\\\\\n\n\n(2x + y - 3)\\mathrm{d}y + (x + 2y - 3)\\mathrm{d}x = 0\\\\\n\n\nM\\mathrm{d}y + N\\mathrm{d}x = 0\\\\\n\n\nM_x = \\frac{\\partial M}{\\partial x} = 2\\\\\n\n\nN_x = \\frac{\\partial N}{\\partial y} = 2\\\\\n\n\\textsf{Since}\\,\\, M_y = N_x\\,\\,\\textsf{the differential equation is exact}\\\\\n\n\n\\frac{\\partial z}{\\partial y} = 2x + y - 3\\\\\n\nz = \\int(2x + y - 3)\\, \\mathrm{d}y\\\\\n\nz = 2xy + \\frac{y^2}{2} - 3y + f(x)\\\\\n\n\n\\frac{\\partial z}{\\partial x} = x + 2y - 3\\\\\n\nz = \\int (x + 2y - 3)\\,\\mathrm{d}x\\\\\n\nz = \\frac{x^2}{2} + 2xy - 3x + f(y)\\\\\n\n\nz = 2xy + \\frac{x^2 + y^2}{2} - 3(x + y)"
Comments
Leave a comment